AB0667 Clinical and immunological features in a monocentric cohort of 305 italian patients affected with systemic lupus erythematosus. (23rd January 2014) - Conti, V.; Perricone, C.; Ceccarelli, F.; Pacucci, V.; Truglia, S.; Miranda, F.; Bartosiewicz, I.; Massaro, L.; Spinelli, F.R.; Alessandri, C.; Valesini, G.; Conti, F.
Abstract : Objectives: To analyze the clinical and immunological features of an Italian cohort of systemic lupus erythematosus (SLE) patients referring to a unique center, and to evaluate their association with specific pattern of disease. Methods: Three hundred five consecutive patients followed from September 2008 to July 2011, were evaluated. All the patients satisfied the 1987 revised criteria of the American College Rheumatology. At each visit, the patients underwent a complete physical examination, and the clinical and laboratory data were collected in a standardized, computerized, and electronically-filled form, which included demographics, past medical history with date of diagnosis, comorbidities, and previous and concomitant. Disease activity was assessed using SLEDAI and ECLAM, while chronic damage was measured with SLICC. Patients were divided into subcathegories according with age at onset: <14 years (group 1), 15-50 years (group 2), >50 years (group 3). Results: At first we evaluated clinical and laboratory features at time of disease onset. Group 1 patients showed more frequently thrombocytopenia (P=0.006) and less frequently arthritis (P=0.028) compared with group 2 patients. Nonetheless, group 1 patients showed less frequently anti-Ro/SSA compared with group 2 and 3 (P=0.04 and P=0.006, respectively). LAC positivity was more prevalent in group 2 patients (P=0.03). Renal involvement was less frequent in group 3 patients (P=0.04). At time of the first visit, mean disease duration was 12.3±18.6 months. Patients with older than 50 years had a significantly lower frequency of renal involvement than those below 50 years (P=0.003, OR=0.14, 95% CI 0.03-0.6). Presence of anti–dsDNA antibodies was associated with renal involvement (P=0.035, OR=1.9, 95% CI 1-3.64) and with neuropsychiatric involvement (P<0.05, OR=2.59, 95% CI 0.97-7). The presence of anti-2GPI antibodies was associated with hematologic manifestations (P=0.01, OR=1.9 95% CI 1.2-5.7). Anti-2GPI and anti-CL (P=0.04, OR=0.5, 95% CI 0.3-0.6) resulted protective for cutaneous involvement (P=0.006, OR=0.3, 95% CI 0.15-0.74). Anti-La/SSB were associated with hematologic involvement (P=0.03, OR=2.45, 95% CI 1-5.7). No differences in clinical and immunological features were observed when dividing the patients according to gender. Conclusions: Our cohort seems to have similar clinical and immunological features when compared with other European cohorts, but Italian patients seem to have a more frequent hematologic involvement and a less frequent neuropsychiatric. We confirm the association between anti-dsDNA antibodies with renal involvement and anti-La/SSB antibodies with cutaneous manifestations. Interestingly, thrombocytopenia was a relatively frequent manifestation at disease onset in younger patients, while renal involvement seems to be a less frequent manifestation at disease onset in older patients. Disclosure of Interest: None Declared